Kontrol Sosial Orang Tua Terhadap Dampak Penggunaan Smartphone Pada Anak MIN 39 Aceh Besar - Miftahul Jannah; Zulfan Zulfan (Jurnal Realitas Sosial, 2025)
Along with the increasing development and use of technology by children, especially school-age children, parents face a major challenge in supervising and controlling their children's use of smartphones. This device is not only a means of entertainment, but also a source of information and social interaction that can have positive or negative impacts on children's development. This study aims to determine the form of parental social control and its impact on children's smartphone use at MIN 39 Aceh Besar. This study uses a descriptive qualitative method with the Social Control theory proposed by Travis Hirschi as a foundation, which includes four main elements: involvement, belief, commitment, and attachment. Data collection techniques were carried out through interviews, direct observation, and documentation. The results of the study showed that parents and have implemented various strategies such as implementing rules with time limits, supervision by setting child features, accompanying children when using smartphones, providing advice, and teaching children how to use smartphone features wisely and teaching social values ​​to children. In addition, active parental involvement is very important in developing children's discipline and boundaries in using technology, as well as good and active communication to maintain children's emotional and mental well-being.